On the issue of planning and risk management in sports - M. A. Yakovlev (Путеводитель предпринимателя)
Every sporting and entertainment event involves a physical risk. The type and level depend on variables such as the type of activity, location, skill level of participants, time and number of viewers. Whatever your event is, it is important that you are prepared for it by managing these risks.Sports and recreation involve a certain level of physical risk. Many sports and recreational activities involve high–speed impacts, extreme effort, exposure to altitude or depth, and environmental factors such as weather. Participants recognize that there is a risk when participating in these activities. At the same time, the organizers are responsible for taking measures to ensure the safety of participants, spectators, paid staff, volunteers and the general public.Effective risk management applies a clear risk identification process, establishes an acceptable risk level and takes steps to maintain risks at this level. Risk management is carried out by assessing potential consequences and probability, developing clear actions and developing a response plan.Successful organizers manage risks rather than avoid them. They focus on goals and security, not just compliance. Through effective risk management, you can minimize the potential costs and obligations associated with event planning, which will make the event safer and more enjoyable.